Bottom‐Up Synthesized Nanoporous Graphene Transistors (Adv. Funct. Mater. 47/2021). (18th November 2021) - Mutlu, Zafer; Jacobse, Peter H.; McCurdy, Ryan D.; Llinas, Juan P.; Lin, Yuxuan; Veber, Gregory C.; Fischer, Felix R.; Crommie, Michael F.; Bokor, Jeffrey
Abstract : Nanoporous Graphene Transistors Bottom‐up synthesis has recently enabled the fabrication of nanoporous graphene with atomically precise pores and consequent uniform band gap. In article number 2103798, Jeffrey Bokor and co‐workers use this strategy to turn molecules into nanoporous graphene, which is subsequently transferred to devices and turned into field‐effect transistors. The switching performance is high and correlates with the degree of structural perfection.